KEDARURATAN KESEHATAN MASYARAKAT DAN PEMBATASAN HAM DALAM PERSPEKTIF HUKUM KETATANEGARAAN INDONESIA - Andi Daffa Patiroi; Riris Ardhanariswari; Manunggal Kusuma Wardaya (Faculty of Law, Parahyangan Catholic University, 2023)
The COVID-19 that spread in early 2020 made countries all over the world declare a state of emergency. In the context of Indonesia, President Joko Widodo declared COVID-19 as a type of disease that causes a public health emergency through Presidential Decree Number 11 of 2020 on March 31, 2020. This study aims to find out the status of public health emergencies from the perspective of Indonesian constitutional law. Furthermore, this research also aims to find out how the state's authority in limiting human rights in public health emergencies is according to human rights law. In its analysis, this research uses a normative juridical method with a statutory approach and a conceptual approach. The results obtained indicate that the status of public health emergency as stated in Presidential Decree Number 11 of 2020 is different from the state of emergency as stated in Article 12 of the 1945 Constitution. As for the limitation of human rights, the state has the authority to limit the human rights of its citizens in the COVID-19 public health emergency.